1987
DOI: 10.4269/ajtmh.1987.36.598
|View full text |Cite
|
Sign up to set email alerts
|

Diarrheal Morbidity and Mortality in Children in the Central African Republic

Abstract: Diarrheal morbidity and mortality in children less than 5 years old were studied in Bangui, Central African Republic, by a cluster survey. We found a high prevalence of diarrheal disease with an estimated annual incidence of 7 episodes of diarrhea per child per year. The estimated annual mortality rate for children less than 5 years old was 28.6 per 1,000 and 85.8 per 1,000 for infants; 51.6% of deaths were reported to be associated with diarrhea. During the survey, stool specimens were collected from 133 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Shigella is a major cause, as reported in Senegal, Djibouti and Zambia, where it represents respectively 11%, 15% and 10.2% of enteropathogenic agents [6][7][8]. A previous study in Bangui in 1983 found only 2.2% of diarrhoea attributable to Shigella (9). Such an increase in prevalence is supported by World Health Organization data, which demonstrates a regular increasing trend of Shigella in sub-Saharan countries in the last ten years [10].…”
Section: Discussionmentioning
confidence: 80%
“…Shigella is a major cause, as reported in Senegal, Djibouti and Zambia, where it represents respectively 11%, 15% and 10.2% of enteropathogenic agents [6][7][8]. A previous study in Bangui in 1983 found only 2.2% of diarrhoea attributable to Shigella (9). Such an increase in prevalence is supported by World Health Organization data, which demonstrates a regular increasing trend of Shigella in sub-Saharan countries in the last ten years [10].…”
Section: Discussionmentioning
confidence: 80%
“…Children comprised the target population in the majority of the studies [6, 7, 12, 13, 25, 26, 28, 67, 68, 70–74, 76, 78, 79, 81, 82, 84–86, 8891, 93–104], although some studies included adults with or without children [69, 75, 77, 80, 83, 87, 92, 105]. …”
Section: The Association Between G Lamblia and Diarrheal Diseasementioning
confidence: 99%
“…Case ascertainment was performed in the community [78, 96], outpatient clinics [6, 25, 28, 69, 73, 76, 81, 82, 91, 97, 102, 103], emergency rooms [83, 90, 95], or hospitals [7, 12, 13, 26, 68, 70–72, 75, 77, 80, 84, 86, 87, 93, 100, 104, 105]. The control subjects without diarrhea were outpatients [6, 13, 25, 28, 67, 69, 72, 73, 76, 80, 81, 89, 91, 95, 97, 101–103] emergency room patients [83], or hospitalized patients [7, 12, 13, 26, 70, 71, 75, 77, 84, 86, 87, 100, 104, 105], but some studies enrolled community controls [68, 78, 82, 93, 96].…”
Section: The Association Between G Lamblia and Diarrheal Diseasementioning
confidence: 99%
See 2 more Smart Citations